2022
DOI: 10.1038/s41398-022-02152-0
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of remission among patients with a major depressive disorder based on the resting-state functional connectivity of emotion regulation networks

Abstract: The prediction of antidepressant response is critical for psychiatrists to select the initial antidepressant drug for patients with major depressive disorders (MDD). The implicated brain networks supporting emotion regulation (ER) are critical in the pathophysiology of MDD and the prediction of antidepressant response. Therefore, the primary aim of the current study was to identify the neuroimaging biomarkers for the prediction of remission in patients with MDD based on the resting-state functional connectivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“… Functional (cont.) Wu et al [ 12 ] 81 MDD -Escitalopram (SSRI) -12 weeks -Seed-based: 36 seeds from emotion regulation networks -Baseline MRI Patients with remission and non-remission were separated with an accuracy of 82%. The FC between the left medial SFG, right IFG, and PCu were the features with the highest discrimination ability.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… Functional (cont.) Wu et al [ 12 ] 81 MDD -Escitalopram (SSRI) -12 weeks -Seed-based: 36 seeds from emotion regulation networks -Baseline MRI Patients with remission and non-remission were separated with an accuracy of 82%. The FC between the left medial SFG, right IFG, and PCu were the features with the highest discrimination ability.…”
Section: Resultsmentioning
confidence: 99%
“…Ye et al (2022) reported increased baseline right angular gyrus FC within the DMN in the remitted group compared with the non-remitted group, which was positively correlated with the reduction of depressive scores [ 8 ]. In addition to the increased FC within the DMN that was associated with better treatment outcomes [ 9 11 ], increased FC between DMN and frontoparietal network (FPN) [ 9 , 10 , 12 ], and somatomotor network (SMN) [ 10 ] was also reported. Additionally, treatment response was associated with increased FC between the right FPN and the posterior DMN, SMN, and somatosensory association cortex (SAC) by Martens et al [ 13 ].…”
Section: Resultsmentioning
confidence: 99%
“…The subjects whose head motion was >2.5 mm maximum translation in any direction of x, y or z or 2.5° of maximum rotation or if their mean FD exceeded 3 SD of the mean value were excluded. 21 …”
Section: Methodsmentioning
confidence: 99%
“…To quantify microhead motions, the ‘bad’ time points were removed from the time series by employing a ‘scrubbing’ method with a frame-wise displacement (FD)20 threshold of 0.5 mm. The subjects whose head motion was >2.5 mm maximum translation in any direction of x, y or z or 2.5° of maximum rotation or if their mean FD exceeded 3 SD of the mean value were excluded 21…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation